ANALISIS KONSEP HADITS PENDIDIKAN ROHANI TENTANG PERASAAN EMOSI H.R Al-BUKHARI - Nuralim, Desi; Nabilah, Chintia; Suharna, Atang; Wartini, Dede; Maslani, Maslani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
According to an Islamic perspective, the hadith narrated by Bukhori ra conveys an important message about true strength. The Prophet Muhammad SAW emphasized that true strength is not just courage in battle, but rather the ability to control oneself, especially when facing negative emotions such as anger. This hadith shows how important it is to manage emotions as part of building strong character in Islam in spiritual education. Through understanding and applying these teachings, Muslims are taught to develop patience, self-control, and inner peace when facing the conflicts and challenges of everyday life. Therefore, this hadith has significant relevance in the context of Islamic spiritual education, which aims to develop individuals who have true strength to face life's trials with patience, peace and calm. The research method used is a qualitative method with a descriptive approach from previous literature sources. By looking at the text and context of the hadith narrated by Bukhori, it emphasizes the importance of having the ability to control oneself when dealing with emotions, especially anger. According to text analysis, strength consists of physical courage and the ability to control oneself in difficult situations. However, context analysis shows that this hadith originates from the life of the Prophet Muhammad SAW in Medina, where Islam developed into an orderly society. Islamic values ​​and customs were included in the social context of the time. Meanwhile, this Hadith aims to inform Muslims about the meaning of strength from an Islamic perspective. The Prophet Muhammad SAW emphasized that true strength does not only come from physical courage in battle, but also from the ability to control emotions, especially anger.